1989
DOI: 10.1172/jci114214
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon gene transcription is negatively regulated by insulin in a hamster islet cell line.

Abstract: Complex interrelationships exist between the four pancreatic islet cell types and their respective secretory products, insulin, glucagon, somatostatin, and pancreatic polypeptide. These hormones are known to interact with the different islet cells and modulate their functions. Insulin inhibits glucagon secretion from the A cell both in vivo and in vitro and, in states of insulin deficiency, high glucagon levels are observed that are normalized by insulin replacement. To determine if insulin also regulates gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 44 publications
9
52
0
1
Order By: Relevance
“…6A, insulin treatment led to a 95, 85, and 90% reduction in the level of expression of Tcf7, Tcf7l1, and Tcf7l2 respectively. Figure 6B shows that insulin treatment led to a significantly reduced expression of gcg, consistent with observation made by J Philippe two decades ago (Philippe 1989(Philippe , 1991. Figure 6C shows that in the pancreas of HFD fed mice, the expression level of Tcf7, Tcf7l1, and Tcf7l2 was significantly lower than those from mice fed with chow diet.…”
Section: Expression Of Tcf7l2 In Pancreatic Tissue and Islets Is Downsupporting
confidence: 86%
“…6A, insulin treatment led to a 95, 85, and 90% reduction in the level of expression of Tcf7, Tcf7l1, and Tcf7l2 respectively. Figure 6B shows that insulin treatment led to a significantly reduced expression of gcg, consistent with observation made by J Philippe two decades ago (Philippe 1989(Philippe , 1991. Figure 6C shows that in the pancreas of HFD fed mice, the expression level of Tcf7, Tcf7l1, and Tcf7l2 was significantly lower than those from mice fed with chow diet.…”
Section: Expression Of Tcf7l2 In Pancreatic Tissue and Islets Is Downsupporting
confidence: 86%
“…Our data demonstrate that secreted glucagon stimulates its own resynthesis via a positive autocrine feedback mechanism. The increase in (prepro)glucagon mRNA levels is only transient, however, and the feedback loop is turned off by a lack of glucagon stimulus, leading to transient activation of protein kinases PKA and PKC in response to rising blood glucose levels, as well as to inhibition of glucagon gene transcription by insulin (33). Interestingly, GLP-1, another product of the (prepro)glucagon gene that is synthesized and secreted by intestinal L cells, is also able to activate the glucagon promoter in αTC1-9 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have demonstrated that the GLUTag cell line responds appropriately to the regulatory factors known to control glu gene expression and GLP-1 synthesis and secretion in primary gut endocrine cells, including cAMP/protein kinase A, glucose-dependent insulinotropic peptide, and bethanechol (26,40,50,51). Likewise, the ␣-TC-1 and InR1-G9 cell lines have been routinely used as ␣ cell models to study glu gene expression and glucagon synthesis and secretion (19,20,30,(52)(53)(54)(55)(56). In these cell lines, for example, glucagon secretion is repressed by retinol and retinoic acid (52) and activated by phorbol esters (54), cytosolic calcium oscillations are inhibited by high glucose, and glu mRNA expression and glucagon synthesis are inhibited by insulin (55).…”
Section: Discussionmentioning
confidence: 99%